logo

Selective Sampling Theorem Proof 📂Probability Theory

Selective Sampling Theorem Proof

Theorem

Let’s assume there is a probability space (Ω,F,P)( \Omega , \mathcal{F} , P) and a supermartingale {(Xn,Fn)}\left\{ ( X_{n} , \mathcal{F}_{n} ) \right\}.

If τ\tau and σ\sigma are bounded stopping times with respect to στ\sigma \le \tau and Fn\mathcal{F}_{n} then E(XτFσ)Xσ a.s. E \left( X_{\tau} | \mathcal{F}_{\sigma} \right) \le X_{\sigma} \text{ a.s.}


  • Being bounded with respect to Fn\mathcal{F}_{n} for τ\tau means, quite literally, that there exists a NNN \in \mathbb{N} such that for all EFnE \in \mathcal{F}_{n} it satisfies τ(E)N\tau (E) \le N.

Description

What the equation essentially says is that when there is a condition στN\sigma \le \tau \le N, the condition of the supermartingale E(Xσ+1F)Xσ a.s. E \left( X_{\sigma +1} | \mathcal{F} \right) \le X_{\sigma} \text{ a.s.} even if changed to τ\tau E(XτF)Xσ a.s. E \left( X_{\tau} | \mathcal{F} \right) \le X_{\sigma} \text{ a.s.} the direction of the inequality is maintained as it is.

Proof

Part 1. 1(σ=b)1(τn)=1(σ=n)\mathbb{1}_{(\sigma = b)} \mathbb{1}_{(\tau \ge n)} = \mathbb{1}_{(\sigma = n)}

Since στ\sigma \le \tau, it follows that (σ=n)(τn)(\sigma = n ) \subset ( \tau \ge n), and 1(σ=b)1(τn)=1(σ=n)\mathbb{1}_{(\sigma = b)} \mathbb{1}_{(\tau \ge n)} = \mathbb{1}_{(\sigma = n)}


Part 2. (τn+1)Fn( \tau \ge n+1) \in \mathcal{F}_{n}

Considering that (τ<n+1)=(τn)Fn( \tau < n+1) = ( \tau \le n ) \in \mathcal{F}_{n} and given (τ<n+1)=(τn+1)c( \tau < n+1) = ( \tau \ge n+1)^{c}, by the definition of sigma-fields, (τn+1)Fn( \tau \ge n+1) \in \mathcal{F}_{n} must follow.


Part 3. Xn1(σ=n)E(XτFn1(σ=n))X_{n} \mathbb{1}_{(\sigma =n)} \ge E \left( X_{\tau} | \mathcal{F}_{n} \mathbb{1}_{(\sigma = n)} \right)

Let’s consider the scenario when n=1,,Nn = 1 , \cdots , N.

Properties of Conditional Expectation: If XX is F\mathcal{F}-measurable, then E(XF)=X a.s.E(X|\mathcal{F}) =X \text{ a.s.}

Due to the properties of conditional expectation and indicator functions, along with Part 1 and 2, for every event AFnA \in \mathcal{F}_{n} AXn1(σ=n)dPAE(XτFn)1(σ=n)dP=AXn1(σ=n)1(τn)dPAE(XτFn)1(σ=n)1(τn)dP=A(σ=n)(τn)XndPA(σ=n)(τn)E(XτFn)dP=A(σ=n)(τn)E(XnFn)dPA(σ=n)(τn)E(XτFn)dP=A(σ=n)(τn)E(XnXτFn)dP=A(σ=n)(τn)(XnXτ)dP \begin{align*} & \int_{A} X_{n} \mathbb{1}_{(\sigma = n)} dP - \int_{A} E \left( X_{\tau} | \mathcal{F}_{n} \right) \mathbb{1}_{(\sigma = n)} dP \\ =& \int_{A} X_{n} \mathbb{1}_{(\sigma = n)} \mathbb{1}_{(\tau \ge n)} dP - \int_{A} E \left( X_{\tau} | \mathcal{F}_{n} \right) \mathbb{1}_{(\sigma = n)} \mathbb{1}_{(\tau \ge n)} dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } X_{n} dP - \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } E \left( X_{\tau} | \mathcal{F}_{n} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } E \left( X_{n} | \mathcal{F}_{n} \right) dP - \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } E \left( X_{\tau} | \mathcal{F}_{n} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } E \left( X_{n} - X_{\tau} | \mathcal{F}_{n} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } \left( X_{n} - X_{\tau} \right) dP \end{align*} Splitting the integral range from (τn)( \tau \ge n) into (τ>n)( \tau > n) and (τ=n)( \tau = n) shows that since (XτXn)=0(X_{\tau} - X_{n}) = 0 from (τ=n)(\tau = n) A(σ=n)(τn)(XnXτ)dP=A(σ=n)(τn+1)(XnXτ)dP+A(σ=n)(τ=n)(XnXτ)dP=A(σ=n)(τn+1)(XnXτ)dP+0 \begin{align*} & \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n) } \left( X_{n} - X_{\tau} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } \left( X_{n} - X_{\tau} \right) dP + \int_{A \cap ( \sigma =n ) \cap ( \tau = n) } \left( X_{n} - X_{\tau} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } \left( X_{n} - X_{\tau} \right) dP + 0 \end{align*} Given that {(Xn,Fn)}\left\{ ( X_{n} , \mathcal{F}_{n} ) \right\} is a supermartingale and XτX_{\tau} is Fn\mathcal{F}_{n}-measurable, it follows that Xτ=E(XτFn) a.s.X_{\tau} = E \left( X_{\tau} | \mathcal{F}_{n} \right) \text{ a.s.} A(σ=n)(τn+1)(XnXτ)dP=A(σ=n)(τn+1)XndPA(σ=n)(τn+1)XτdPA(σ=n)(τn+1)E(Xn+1Fn)dPA(σ=n)(τn+1)E(XτFn)dP=A(σ=n)(τn+1)E(Xn+1XτFn)dP=A(σ=n)(τn+1)(Xn+1Xτ)dPA(σ=n)(τn+2)(Xn+2Xτ)dPA(σ=n)(τN)(XNXτ)dP=A(σ=n)(τ=N)(XNXτ)dP=0 a.s. \begin{align*} & \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } \left( X_{n} - X_{\tau} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } X_{n} dP - \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } X_{\tau} dP \\ \ge& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } E \left( X_{n+1} | \mathcal{F}_{n} \right) dP - \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } E \left( X_{\tau} | \mathcal{F}_{n} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } E \left( X_{n+1} - X_{\tau} | \mathcal{F}_{n} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +1 ) } \left( X_{n+1} - X_{\tau} \right) dP \\ \ge& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge n +2 ) } \left( X_{n+2} - X_{\tau} \right) dP \\ & \vdots & \\ \ge& \int_{A \cap ( \sigma =n ) \cap ( \tau \ge N ) } \left( X_{N} - X_{\tau} \right) dP \\ =& \int_{A \cap ( \sigma =n ) \cap ( \tau = N ) } \left( X_{N} - X_{\tau} \right) dP \\ =& 0 \text{ a.s.} \end{align*} Then, starting from the initial equation AXn1(σ=n)dPAE(XτFn)1(σ=n)dP a.s. \int_{A} X_{n} \mathbb{1}_{(\sigma = n)} dP \ge \int_{A} E \left( X_{\tau} | \mathcal{F}_{n} \right) \mathbb{1}_{(\sigma = n)} dP \text{ a.s.} and since AF,Afdm=0    f=0 a.e.\displaystyle \forall A \in \mathcal{F}, \int_{A} f dm = 0 \iff f = 0 \text{ a.e.}, Xn1(σ=n)E(XτFn)1(σ=n) a.s. X_{n} \mathbb{1}_{(\sigma =n)} \ge E \left( X_{\tau} | \mathcal{F}_{n} \right) \mathbb{1}_{(\sigma = n)} \text{ a.s.}


Part 4. E(XτF)Xσ a.s. E \left( X_{\tau} | \mathcal{F} \right) \le X_{\sigma} \text{ a.s.}

Properties of Stopping Times: If ZnZ_{n} is a FnF_{n}-measurable function, then Zn1σ=nZ_{n} \mathbb{1}_{\sigma = n} is a function measurable with respect to both Fσ\mathcal{F}_{\sigma} and Fn\mathcal{F}_{n}. Moreover, Zn1(σ=n)=Zσ1(σ=n)Z_{n} \mathbb{1}_{(\sigma = n)} = Z_{\sigma} \mathbb{1}_{(\sigma = n)} holds true.

According to the properties of stopping times and Part 3, for n=1,,Nn=1,\cdots, N Xn1(σ=n)E(XτFn)1(σ=n)    Xσ1(σ=n)E(XτFσ)1(σ=n)    XσE(XτFσ) \begin{align*} & X_{n} \mathbb{1}_{(\sigma =n)} \ge E \left( X_{\tau} | \mathcal{F}_{n} \right) \mathbb{1}_{(\sigma = n)} \\ \iff & X_{\sigma} \mathbb{1}_{(\sigma =n)} \ge E \left( X_{\tau} | \mathcal{F}_{\sigma} \right) \mathbb{1}_{(\sigma = n)} \\ \iff & X_{\sigma} \ge E \left( X_{\tau} | \mathcal{F}_{\sigma} \right) \end{align*}